The Structure and Function of Israeli Employers’ Associations - Shirom, Arie; Jacobson, Dan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
The first part of this article is devoted to a brief description of the ideological, political, economic and legal environment of the employers' associations in Israel. Then, the current structures of the three major associations are discussed, and their external and internal relations are analyzed. Finally, some tentative conclusions emanating from the report are presented, and several possible implications of the Israeli experience for employers' associations in other countries are suggested.